Figure 11 from: Wallin H, Kvamme T, Bergsten J (2017) To be or not to be a subspecies: description of Saperda populnea lapponica ssp. n. (Coleoptera, Cerambycidae) developing in downy willow (Salix lapponum L.). ZooKeys 691: 103-148. https://doi.org/10.3897/zookeys.691.12880 - Wallin, Henrik; Kvamme, Torstein; Bergsten, Johannes (Zenodo, 2017)
Figure 11 - Hind wings. a ♀ Saperda populnea populnea (Linnaeus, 1758) reared from Populus tremula L., Uppland, Knivsta, Sweden. A AP vein B AA vein C CuA vein D AA3+4 vein E CuA3+4 vein F Mp4 vein G Mp3 vein H medial spur vein I RA vein J MP vein K radial cell L RP-MP vein b ♀ Saperda populnea lapponica ssp. n. reared from Salix lapponum L., Trysil: Ljørdalen Norway c ♀ Saperda populnea lapponica ssp. n. reared from Salix lapponum L., Luleå Lappmark, Gallugas 20 km W. Kiruna, Sweden. Scale bar 10 mm.